Proceedings of the 1st International Conference on Information Interaction in Context - IIiX 2006
DOI: 10.1145/1164820.1164825
|View full text |Cite
|
Sign up to set email alerts
|

Studying human judgments of relevance

Abstract: This paper discusses the ways participants in a two-year ethnographic study judged relevance when engaged in searching and research tasks. Two experienced academics have been observed evaluating informative artefacts (documents, citations or other representations) encountered in the course of their own research projects. This study sought to explore the criteria and clues used to make decisions about the relevance of retrievable items. In presenting some of the findings from this longitudinal study, the paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Indeed, there are a number of perceptual stimuli that are more likely than others to get our attention by distracting the rest. In addition, the brain is not able to e®ectively track multiple tasks at once, but it knows to move very quickly from one task to another or remember a primary task while others are conducted [24]. More speci¯cally, in the context of interaction between the brain and images, the intention of¯nding a certain class of images is strongly related to consciousness.…”
Section: Negative Relevance Feedback: Semantic Contributionmentioning
confidence: 99%
“…Indeed, there are a number of perceptual stimuli that are more likely than others to get our attention by distracting the rest. In addition, the brain is not able to e®ectively track multiple tasks at once, but it knows to move very quickly from one task to another or remember a primary task while others are conducted [24]. More speci¯cally, in the context of interaction between the brain and images, the intention of¯nding a certain class of images is strongly related to consciousness.…”
Section: Negative Relevance Feedback: Semantic Contributionmentioning
confidence: 99%
“…The XML documents were parsed and the textual content of each XML element was indexed using Lucene. 1 (as separate fields, with stemming and without stopword removal). In this way elements can be searched, and we can also retrieve the full text content of a specified element.…”
Section: Experimental Setup and Preprocessingmentioning
confidence: 99%
“…the clues that researchers use to make relevance decisions, and have been found beneficial for exploring digital libraries [1,5]. As manual assignment of keyphrases is a tedious process, various methods to automatically suggest keyphrases have been proposed [13], that select phrases based on features capturing usage of the phrase.…”
mentioning
confidence: 99%
“…), publishing date (e.g., year), and its text. These attributes can contain specific words, i.e., terms that can be recognized by the information seeker as relevant and trigger the formulation of refined search queries (Barry, 1994;Anderson, 2006).…”
Section: Information Seekingmentioning
confidence: 99%
“…Studies conducted by (Anderson, 2006) reported that it was difficult to find and specify appropriate terms to define more precise search queries, especially, if an information seeker was unfamiliar with the terminology of the problem domain, or if this terminology changed over time.…”
Section: Information Seekingmentioning
confidence: 99%